Strategies for connecting low income communities to the creative economy through play: two case studies in Northern England. Issue 2 (4th May 2018) - Symons, Jessica; Hurley, Ursula
ABSTRACT: This ground-breaking research defines a new approach for engaging low income and disenfranchised communities in the creative economy. The authors propose that demystifying creativity and reframing it as an adaptive productive process can lead to a flourishing of aspiration and potential among target communities. Through research in a low income community and among disabled people in Northern England, the authors found that focusing on rubrics of exploration, play and 'purposeful meandering' tackled anxieties around creative production and a lack of confidence and self-belief. This emphasis on all people as cultural producers however needs to connect with clearer pathways into the creative industries.